Josephson effect in a weak link between borocarbides - Kolesnichenko, Yu.A.; Shevchenko, S.N. (Физика низких температур, 2005)
A stationary Josephson effect is analyzed theoretically for a weak link between borocarbide superconductors.
It is shown that different models of the order parameter result in qualitatively different
current-phase relations.